(untitled) (Ameghiniana, 2014)
The Ponón Trehué Formation is discontinuously exposed 42 km South of San Rafael city, in the Sierra Pintada (Southern Mendoza Province). In the area olistoliths, megaconglomerates with gray limestones blocks, conglomerates, sandstones, green shales, ca1careous sandstones, limestones and black shaIes are present. These deposit associations contain a fossil community with: trilobites, brachiopods, crinoids, porifera spicules, ostracods and conodonts. Conodonts belong to the Pygodus serra Zone and Pygodus anserinus Zone (Upper Llanvirinian). The Pygodus sena Zone bears Eoplacognathus robustus Bergstorn allowing definition of the Eoplacognathus robustus Subzone.